Kepemimpinan Inovatif Dalam Mewujudkan Inovasi Pelayanan Publik - Harditya Bayu Kusuma (Jurnal Transformasi Administrasi, 2017)
Bureaucracy reform is an effort in the implementation of the system of government and public services are geared to achieve the performance of a professional bureaucracy, responsive and accountable. Reform of the bureaucracy that has taken place in Indonesia has given birth to innovative leadership that succeeded in realizing innovative public services. This paper has the objective to to describe and analyze innovative leadership by several heads of regions that have succeeded in realizing innovative public services. Data collection method in this research done through the study of literature (desk research). This study decrypt and analyze innovative leadership as: Ridwan Kamil (Mayor of Bandung), I.B. Dharmawijaya Rai Mantra (Mayor of Denpasar) and Nurdin Abdullah (Regent of Bantaeng). Innovative leadership prerequisites for innovation in public services include: visionary and have the creativity, enthusiasm and self-confidence, goal orientation and service to the community, collaboration and networking with various parties, and the use of Information and Communication Technology.